1978
DOI: 10.7589/0090-3558-14.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Brucellosis in Elk I. Serologic and Bacteriologic Survey in Wyoming

Abstract: Incidence of brucellosis in elk (Cervus canadensis) on two winter feedgrounds in Wyoming was examined over a 5-year period by testing serum samples using the standard plate agglutination (SPT) buffered Brucella antigen (BBA), rivanol (Riv) and complement fixation (CFT) tests. Thirty-one percent of 1,165 elk were positive by defined criteria. Considering each test individually, only 29% (106) of 370 positive sera would have been classified as reactors by the SPT, 83% (307) by the BBA test and 86% (314) by the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…They were never subjected to the same scrutiny for validation as present day primary binding assays. As well, the data reported in the literature (Thorne et al, 1978;Davis et al, 1990;Nicoletti, 1992) suggests that no single test could be relied upon to definitively diagnose brucellosis in bison.…”
Section: Discussionmentioning
confidence: 90%
“…They were never subjected to the same scrutiny for validation as present day primary binding assays. As well, the data reported in the literature (Thorne et al, 1978;Davis et al, 1990;Nicoletti, 1992) suggests that no single test could be relied upon to definitively diagnose brucellosis in bison.…”
Section: Discussionmentioning
confidence: 90%
“…iseases shared between wildlife and domesticated farm animals, such as brucellosis (1) and bovine tuberculosis in white-tailed deer (2), are notoriously difficult to manage. When wild animals are involved in the epidemiology of a disease which affects domestic animals, the effects on disease spread and control can be profound.…”
mentioning
confidence: 99%
“…Serosurveys of female elk on feedgrounds in Wyoming revealed that approximately one-third were testpositive (Thorne et al, 1978;Morton et al, 1981); therefore, it is important to avoid translocation of elk with any link to the infected free-ranging elk herds in the Greater Yellowstone Area. Outside of the Greater Yellowstone Area, free-ranging elk do not appear to be infected with brucellosis (Adrian and Keiss, 1977;McCorquodale and DiGiacomo, 1985).…”
Section: High Risk Infectious Agents and Ectoparasitesmentioning
confidence: 99%